2017
DOI: 10.1200/jco.2017.35.4_suppl.276
|View full text |Cite
|
Sign up to set email alerts
|

Orally administered CCR2 selective inhibitor CCX872-b clinical trial in pancreatic cancer.

Abstract: 276 Background: CCR2 inhibition decreases tumor-associated macrophages and Treg cells, and increases CD8+ and CD4+ T cells in pancreatic tumors. Single oral doses of 150 mg CCX872-B were well tolerated in patients with pancreatic cancer. The first stage results of the multiple dose part of this study are presented. Methods: Patients with locally advanced or metastatic pancreatic cancer, ECOG score ≤ 2 were studied. Patients received FOLFIRINOX (fluorouracil [5-FU], leucovorin, irinotecan, oxaliplatin) q2weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Our findings demonstrate that Candida PAMPs initiate arteritis by activating TRMs in the aortic root and inducing chemokine and cytokine production in a mouse model of vasculitis resembling KD. Several case reports have shown promising results using the IL-1R antagonist Anakinra to treat KD (57,58) and new therapeutics that target the CCL2/CCR2 chemokine axis are currently in clinical trials for cancer (59,60). Finally, Syk inhibitors are available and have been in clinical trials for the treatment of rheumatoid arthritis (61).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings demonstrate that Candida PAMPs initiate arteritis by activating TRMs in the aortic root and inducing chemokine and cytokine production in a mouse model of vasculitis resembling KD. Several case reports have shown promising results using the IL-1R antagonist Anakinra to treat KD (57,58) and new therapeutics that target the CCL2/CCR2 chemokine axis are currently in clinical trials for cancer (59,60). Finally, Syk inhibitors are available and have been in clinical trials for the treatment of rheumatoid arthritis (61).…”
Section: Discussionmentioning
confidence: 99%
“…Encouragingly, preliminary clinical benefit has been observed in a phase Ib trial evaluating the safety and effectiveness of CCX872, an orally administered CCR2 inhibitor, in patients with advanced pancreatic cancer. According to the data announced in January 2018, 29% patients receiving CCX872 and FOLFIRINOX combination therapy survived at the 18th month, more favorable than previously published OS rates of 18.6% at 18th month using FOLFIRINOX alone [132, 133]. Furthermore, a number of agents, such as CCL2 inhibitor bindarit, anti-CCL2 mAb carlumab, CSF1 inhibitor GW2580, and dequalinium-14, have been confirmed of potent and sustained anti-tumor activities via declining macrophages infiltration in a battery of cell lines and xenograft models [156160].…”
Section: Potential Strategies Targeting Macrophagesmentioning
confidence: 99%
“…It was reported that both small molecular inhibitors and antibodies targeting either CCL2/CCR2 or CSF-1/CSF-1R signaling axis obviously inhibited the mobilization of monocytes and macrophages accumulation in tumor sites. As a matter of fact, several inhibitors and antibodies targeting the TAM recruiting factors are being evaluated in early clinical trials across various types of tumor [132, 133, 154, 155]. For example, emactuzumab (RG7155) is a novel humanized antibody targeting CSF-1R in both ligand-dependent and ligand-independent manners [154].…”
Section: Potential Strategies Targeting Macrophagesmentioning
confidence: 99%
“…NOX-E36 therapy in a mouse tumor model inhibited the infiltration of tumor-associated macrophages leading to significant changes of the TME and a reduction in liver tumor burden (126). The small molecule inhibitor CCX-872, which targets CCR2, is currently in the clinic for the treatment of patients with advanced and metastatic pancreatic cancer (NCT02345408), and data from the ongoing Phase Ib trial demonstrated promising safety and overall survival with the CCX872 and FOLFIRINOX combination therapy compared to FOLFIRINOX alone (127, 128).…”
Section: Therapeutic Targeting Of Myeloid Populations In the Tmementioning
confidence: 99%